Assessement on the prophylactic and therapeutic potential of the antisense oligodeoxynucleotide To Icam-L In Acute renal failure. - Zubaid, Munavvar (Universiti Sains Malaysia, 2003)

(untitled)
Ischaemia-reperfusion injury refers to injury that occurs in cells or tissues when the particular tissue region/organ is subjected to a prolonged period of oxygen deprivation (ischaemia), followed by immediate reoxygenation (reperfusion). It has been well documented that prolonged ischaemia is capable of causing cell swelling, vasoconstriction and rapid tissue necrosis (Thadani et.al., 1996).